Kebijakan Office Channeling Dan Perkembangan Perbankan Syariah Serta Penyaluran Pembiayaan Usaha Kecil Menengah Di Indonesia (The Office Channeling Policy, the Development of Islamic Banking, and SMEs Financing in Indonesia) - Uding Sastrawan; M. Syamsun; M. Najib (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2013)
This research presents Islamic banking which continuously experience growth in the banking system in Indonesia, especially after Bank Indonesia regulation (office channeling) is applied. The presence of Islamic banking is expected to strengthen the SMEs in accessing the business financing with the concept of profit and loss sharing.  This research was done to find out whether the increasing development of Islamic banking give a positive response in the SMEs sector financing and other variables in line with the rising of Islamic banking portfolio. The study was based on secondary data and mostly collected from the Annual reports published by Bank Indonesia.  Method of Vector Autoregression (VAR) and inferential statistics were used for data analysis. The result suggested that the development of Islamic banking was influenced by the variable of operational expenses ratio to operational revenue (BOPO), financing in SMEs sector (PYD), depositor funds (DPK), non performing financing (NPF), number of worker (PKJ), unless asset growth (GAST).Key words: Islamic banking, Small and medium enterprises (SMEs), Vector autoregression (VAR)